The Accumulation Of Islamic Values In The Educational and it’s Impact On Student’s Social Life (A Case Study at Diniyah Limo Jurai Islamic Boarding School, Agam) - Fajar Illahi (Jurnal Kajian dan Pengembangan Umat, 2026)
This study aims to analyze the accumulation of Islamic values in the educational process and its impact on the social life of students at Diniyah Limo Jurai Islamic Boarding School, Sungai Pua District, Agam Regency. The study is motivated by the crucial role of Islamic education in shaping students’ character, morality, and social awareness amidst the challenges posed by globalization, technological advancement, and the transformation of societal values. This research employed a field research method with a qualitative approach and a case study design. Data were collected through participant observation, in-depth interviews, documentation, and questionnaires distributed to 20 students selected as research respondents. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the accumulation of Islamic values occurs systematically, continuously, and integratively across all aspects of boarding school life through formal learning activities, teachers’ role modeling, worship habituation, supervision, and collective social interactions. The dominant Islamic values internalized by students include honesty, discipline, responsibility, ukhuwah Islamiyah (Islamic brotherhood), humility (tawadhu’), independence, and social concern. The internalization of these values has a positive impact on students’ social lives, reflected in improved manners, social solidarity, empathy, cooperation skills, and adaptability within society. Questionnaire results indicate that 50% of respondents strongly agreed, 40% agreed, and 10% were neutral regarding the effectiveness of the boarding school education in shaping students’ character and social behavior. This study concludes that Diniyah Limo Jurai Islamic Boarding School has been effective in integrating Islamic values into students’ social lives, thereby fostering a generation that is religious, morally upright, responsible, and socially conscious amidst the dynamics of modern society.